Students’ understanding of legal citizenship and co-citizenship concepts - Kerenina K. Dansholm (Nordic Journal of Comparative and International Education, 2022)
This article presents findings from a research project aimed at exploring youth understandings of two Norwegian words for citizen: statsborger and medborger, translated as legal citizen and co-citizen. The topic was explored through group interviews with 10th grade students in three schools. The findings are analysed through the lens of subject positions and capabilities, with the results showing that students appropriate categories and storylines within public debate in order to frame different citizen subject positions as either one of ‘us’ or ‘them’. Dichotomies and overlaps are also visible in descriptions of citizen capabilities as either legal, ideal, or societal. Legal capabilities, understood as the juridically defined rights of majority and minority legal citizens and co-citizens, are less clear to students and are at times obscured by societal capabilities, or the rhetoric within public debate which may hinder minority capabilities. Additionally, ideal capabilities, or democratic values, often stand in conflict with the rhetoric of public debate. The main implication of these research findings is that a citizenship lens allows for a nuanced exploration of citizen subject positions and attendant capabilities within a democracy, including exploration of the challenges that minority citizens may face. Being explicit about the who (subject position), what (categories), and how (storylines) of democratic participation will allow students a more critical understanding of citizenship than the predominantly values centred discussions which are often a staple of citizenship education.